Pengembangan Bahan Ajar Berbasis Pendekatan Pendidikan Matematika Realistik Terintegrasi Multimedia Untuk Meningkatkan Kemampuan Spasial Siswa Pada Materi Bangun Ruang - PURBA, RAHEL DOMINGGO (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2025)
In order to improve student’s spatial abilities in the material of spatial figures (cubes and cuboids), teachers should develop learning innovations, one of which is through the use of teaching materials based on the Realistic Mathematics Education approach integrated with multimedia. This study aims to: (1) determine the quality of the teaching materials developed in terms of validity, practicality, and effectiveness; and (2) determine the increase in student's spatial abilities after participating in learning using the developed teaching materials. This study uses the ADDIE development model with subjects of class VIII-E students of SMP Negeri 2 Satu Atap Patumbak, while the research object is teaching materials based on the Realistic Mathematics Education approach integrated with multimedia. The research instruments used are questionnaires and tests. The results of the study show that: (1) the teaching materials developed are valid based on the assessment of material experts with an average score of 4.5 and media experts with an average score of 4.46, with a very feasible category; (2) the practicality of the teaching materials is stated to be very practical with a practicality value range of 80≤V_p≤100; (3) the effectiveness of the teaching materials with the achievement of classical learning completeness of 90%, average individual completion of 89.5, positive student responses to effectiveness, and a significant increase in spatial ability, from an average pretest score of 28.1 to 89.5 in the posttest. An increase of 0.87 with a high category in the N-Gain analysis results. Keyword: Teaching Materials, ADDIE, Realistic Mathematics Education Approach, Multimedia, Spatial Ability.